2005
DOI: 10.1103/physrevb.72.121401
|View full text |Cite
|
Sign up to set email alerts
|

Surface dynamics of a thin polystyrene film probed by low-energy muons

Abstract: Low-energy muons have been used to probe the local motion in a thin-film sample of polystyrene as a function of depth below the free surface. The muon spin relaxation in zero magnetic field is dominated by a muoniated radical state which is formed on the polystyrene ring. The muon spin-relaxation rate is found to be highly sensitive to the dynamical state of the polymer, and provides a local probe of changes in the dynamical correlation time around the glass transition. When high-energy muons are used to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
1
25
2
Order By: Relevance
“…The dependence of T g on the mean implantation depth below the free surface is very similar for both analysis methods and shows significant suppression with respect to the bulk value for depths of 20 nm and below. The fractional suppression of T g at the surface is of order 20%, which is comparable with that seen in our other LEM studies of PS [10] and PB [15], as well as matching the reduction found at a free polymer surface in molecular dynamics simulations [23]. The length scale for this surface T g suppression is comparable to the random coil end-to-end distance R EE for this molecular weight of polymer.…”
Section: Data For Pdmssupporting
confidence: 73%
See 3 more Smart Citations
“…The dependence of T g on the mean implantation depth below the free surface is very similar for both analysis methods and shows significant suppression with respect to the bulk value for depths of 20 nm and below. The fractional suppression of T g at the surface is of order 20%, which is comparable with that seen in our other LEM studies of PS [10] and PB [15], as well as matching the reduction found at a free polymer surface in molecular dynamics simulations [23]. The length scale for this surface T g suppression is comparable to the random coil end-to-end distance R EE for this molecular weight of polymer.…”
Section: Data For Pdmssupporting
confidence: 73%
“…an environment without unpaired electronic spins. This is in contrast to the two earlier LEM reports on PS that used paramagnetic muoniated radicals as the probe states [10,13].…”
Section: Introductioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Is there an alternative method for evaluating heterogeneous dynamics without resorting to labeling or multilayered methods? Pratt et al [69] studied the dynamics of polymer thin films at different positions in a polymer thin film using slow muons with different incident energies. The advantage of their method is that the dynamics at the desired position in a thin film can be probed just by changing the incident muon energy, which corresponds to changing the interpenetration depth in the thin film.…”
Section: Discussionmentioning
confidence: 99%